PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN PADA CV. SINAR PAPUA - Sofia, Susetyowati; Rahayu, Agilistya; Hasanawati, Nur Intan (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to determine the effect of the marketing mix on the decision to purchase housing at CV. Sinar Papua. In this study, a sample of 45 respondents was taken using an purposive sampling technique. This study uses a descriptive quantitative research method. Which data collection techniques are carried out through direct observation and surveys obtained by distributing questionnaires, interviews, and documentation to housing consumers at CV. Sinar Papuarelating to the purchase decision on the housing. This study uses the SPSS 20 application program. Based on the results of the t-test the effect of each marketing mix variable consisting of Product, Price, Promotion and Location has a significant value below 0.05. So it can be concluded that H0 is rejected and Ha is accepted, which means that Product, Price, Promotion and Location affect the Housing Purchase Decision at CV. Sinar Papua. And based on the results of the f test it can be concluded that Product, Price, Promotion and Location jointly influence the Housing Purchase Decision at CV. Sinar Papuais in accordance with the f test where fcount > ftable (11.760 > 3.226).